Prevalence of cataract in adult Down's syndrome patients aged 28 to 83 years - Puri, Basant K (BioMed Central, 2007)
BACKGROUND: Age-related cataract is the major cause of blindness in humans throughout the world. The majority of previous studies of cataract in Down's syndrome (which usually results from trisomy 21) have reported that the prevalence of this ocular abnormality is higher for a given age range than in the general population. The objective of the present study was to study the prevalence of cataract in a well-defined population of adults with Down's syndrome. METHODS: An in-patient population of 68 adults (35 males and 33 females) with Down's syndrome, aged between 28.9 and 83.3 years, underwent ophthalmological examination for the presence of cataracts. RESULTS: Overall, the prevalence of cataract was 16.2%, with no significant difference in the prevalence between males (17.1%) and females (15.2%). In those aged between 45 and 64 years, the prevalence was 16.7%, rising in those aged between 65 and 75 years to 28.6%. CONCLUSION: Compared with the general population, the prevalence of cataract in Down's syndrome was raised in those aged 45 to 64, but not in those aged 65 to 75 years; the latter might be a function of the relatively small number of patients in this age group. The increased prevalence of cataract found in those in the 45- to 64-year-old age group may be the result of increased levels of the copper- and zinc-containing superoxide dismutase enzyme (CuZnSOD), in turn resulting from the location of the associated five exons of SOD1 on chromosome 21. These elevated levels of superoxide dismutase may give rise to increased levels of reactive species, including hydrogen peroxide and hydroxyl radicals, which may increase the risk of cataractogenesis. It is suggested that nutritional supplementation with antioxidants may therefore help reduce the prevalence of cataract in Down's syndrome.